2015
DOI: 10.2458/azu_rc.57.18153
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Large and Ultra-Small Δ14C Measurements in Core Top Benthic Foraminifera from the Okhotsk Sea

Abstract: ABSTRACT. The radiocarbon activity of benthic foraminifera was investigated in surface sediments from a high deposition rate location at a depth of 1000 m in the Okhotsk Sea. Sediments were preserved and stained with Rose Bengal to identify foraminifera that contain cytoplasm. The benthic fauna at this site is dominated by large specimens of Uvigerina peregrina, and bulk samples (~150 individuals) of stained and unstained specimens were dated. The stained sample was about 240 14 C yr younger than the unstained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Many recent such studies (e.g. Barker et al, 2015;Caley et al, 2012;Simon et al, 2016) use tuning to the LR04 (Lisiecki and Raymo, 2005) benthic stack to produce an age-depth chronology. We have rerun our single-foraminifera sedimentation simulation using the average SAR of LR04 (3.9 cm ka −1 ) and found that one could expect a relative 68.2 % age range of −1330 to 2950 yr for discrete 1 cm depth intervals.…”
Section: Consequences For Existing Studies Using Long-standing Geochrmentioning
confidence: 99%
“…Many recent such studies (e.g. Barker et al, 2015;Caley et al, 2012;Simon et al, 2016) use tuning to the LR04 (Lisiecki and Raymo, 2005) benthic stack to produce an age-depth chronology. We have rerun our single-foraminifera sedimentation simulation using the average SAR of LR04 (3.9 cm ka −1 ) and found that one could expect a relative 68.2 % age range of −1330 to 2950 yr for discrete 1 cm depth intervals.…”
Section: Consequences For Existing Studies Using Long-standing Geochrmentioning
confidence: 99%
“…These authors suggest that measurements of individual foraminiferal tests would allow for the magnitude of the bioturbation effect to be investigated in different sedimentary settings. To demonstrate our ability to measure small numbers of foraminiferal tests, we analyzed live-stained and unstained benthic foraminifera (Uvigerina) from the sediment-water interface from the Sea of Okhotsk (Keigwin and Gagnon 2015) and compared the results with previously measured bulk 14 C dates ( Figure 10). The bulk 14 C ages of stained (1530 ± 25 yr BP) and unstained (1770 ± 65 yr BP) tests were measured on 2.5 mg CaCO 3 , or approximately 150 individual tests.…”
mentioning
confidence: 99%
“…There is reasonable agreement between small numbers (three individuals that generated 12 µg C) of stained foraminifera and the bulk 14 C age, yet greater variability with the unstained comparison results. This variability issue, along with procedures used and other details are specifically outlined in Keigwin and Gagnon (2015). Error bars on ultra-microscale samples are inflated due to the relatively low count rates measured on the samples before the graphite in each target was completely ionized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, high resolution sampling of core depth does not necessarily translate into high resolution sampling of time. Researchers are aware that the concealment of intra-sample age heterogeneity can pose problems for the age-depth model method (Bard, 2001;Keigwin and Gagnon, 2015;Löwemark and Grootes, 2004;Löwemark and Werner, 2001; 45 Pisias, 1983;Ruddiman and Glover, 1972), which can potentially lead to incorrect interpretation of temporal climate offsets, or apparent 14 C age offsets between different species and/or sizes of foraminifera that are, in fact, an artefact of PDSM (Löwemark et al, 2008;Löwemark and Grootes, 2004). With these problems in mind, researchers seeking to reconstruct rapid (i.e.…”
mentioning
confidence: 99%